Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1159/000337644
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic Squamous Cells Are Frequently Present in Urine Cytology Specimens of Patients with High-Grade Urothelial Carcinoma

Abstract: Background: In urothelial carcinoma (UCA), squamous differentiation (SqD) occurs mainly in high-grade UCA with invasion. Therefore, we sought to determine the frequency of dysplastic squamous cells (DSC) in urine specimens obtained from patients with high-grade UCA asking if DSC could serve as a surrogate marker for high-grade UCA. Design: We searched for cases with a histologic diagnosis of high-grade UCA and available concurrent cytology, yielding 93 surgical specimens (including 71 biopsies, 12 cystectomies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Papanicolaou and Marshall first described urine cytology in 1945 and since then, it has acquired prime importance in the screening and follow‐up of patients with urothelial carcinoma (UC) . Urine cytology is the most specific adjunctive tool in addition to cystoscopy for the surveillance of bladder tumour .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papanicolaou and Marshall first described urine cytology in 1945 and since then, it has acquired prime importance in the screening and follow‐up of patients with urothelial carcinoma (UC) . Urine cytology is the most specific adjunctive tool in addition to cystoscopy for the surveillance of bladder tumour .…”
Section: Introductionmentioning
confidence: 99%
“…Urine cytology has high variability in diagnostic accuracy especially in the identification of low‐grade UC (LGUC) as reported in studies conducted worldwide …”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have previously evaluated ASC in urine cytology and found that they rarely occurred, with a reported incidence of ASC in 0.3%-0.9% of urine specimens. 1,2,5 In our study, ASC were seen in 0.15% of urine specimens; but we believe this rate under-represented the true incidence of ASC in urine cytology because ASC were not initially reported in 33 of 91 patients (36%) in our current cohort (Figure 1). A similar observation was made by others.…”
Section: Discussionmentioning
confidence: 58%
“…4 There is limited available literature on the clinical significance of ASC in urine cytology, which did not objectively evaluate the grading of ASC and/or their correlation with associated urothelial cell abnormality (UCA). 1,2,5,6 The Paris System for Reporting Urinary Cytology (TPS) only recently addressed ASC but provided no corresponding risks of HG malignancy (ROHMs). 7 The objective of the current study was to evaluate urine cytology cases with ASC, objectively grade the squamous atypia, and correlate the findings with accompanying UCA and ROHMs.…”
Section: Introductionmentioning
confidence: 99%
“…e deformable particles of SQD-98 have strength and elasticity that display dual functions of expansion and compaction under the pressure difference. ese properties improve the stability of the plugging layer and produce a good sealing effect [26].…”
Section: Laboratory Evaluation Of Plugging With Lcmmentioning
confidence: 99%